The Increase of Drop Out Rate on Contraceptives Usage in Central Sulawesi (Raw Data Analysis of 2017 Indonesian Demographic and Health Survey (IDHS)) - Surayya, Surayya; Sari, Dyah Fitria Kartika; Jaya, Budiman (STRADA : Jurnal Ilmiah Kesehatan, 2020)
This study discusses the increase of drop out rate on contraceptives usage and its various underlying factors in the use of family planning in Central Sulawesi as one of many phenomena that occurs in the community. Logistic regression results of 2017 Indonesian Demographic and Health Survey on contraceptives usage data showed that injection had the highest drop out rate (31.9%), followed by Pills (11.9%), coitus interruptus (4%), and implant (2.4%). Some contraceptives methods that had below 2% drop out rate are periodic abstinence (1.8%), male condoms (1.3%), IUD (1%), LAM method (0.5%) and other traditional methods (0.3%). The high drop out rate of contraceptive usage will affect the continuity of the Family Planning program.